South Africa's energy crisis : reconciling economic growth with environmental protection - Bagley, Constance E.; Aqeel, Haris; Zlotnicka, Eva T. ([London] : SAGE, 2016)
In October 2007, chaos ensued when traffic lights in South Africa's famed commercial center, Johannesburg, failed without warning. That the cause was a power line fault only underscored how strained South Africa's energy system had become. Severe blackouts continued until the summer of 2008, creating widespread socioeconomic damage and stifling the country's growth. This case study discusses this topic.
Originally Published in: Bagley, C. E., Aqeel, H., & Zlotnicka, E. T. (2011). South Africa's Energy Crisis: Reconciling Economic Growth with Environmental Protection. 11-015. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Economic development -- Environmental aspects -- Case studies; Coal-fired power plants -- South Africa -- Case studies; Energy policy -- South Africa